Answer:
for (f+g)(x): 7x + 3; x = -3/7
for (f-g)(x): -3x - 3; x = -1
Explanation:
(f+g)(x) = (2x+7)+(5x-4)
Eliminate parentheses.
2x + 7 + 5x -4
Combine like terms.
7x + 3
If you are solving for x, move the 3 to the other side.
7x = -3.
Then divide each side by 7.
x = -3/7
(f-g)(x) = (2x+7) - (5x -4)
Distribute the negative.
(2x+7) + (-5x+4)
Eliminate parentheses.
2x + 7 - 5x - 4
Combine like terms.
-3x -3
If you are solving for x, move the -3 to the other side.
-3x = 3
Then divide each side by -3.
x = -1.